Synthesis and Characterization of Heparin-Doped Polypyrrole Coatings Using an Electrochemical Quartz Crystal Microbalance (EQCM) - Flamini,D. O. (2022)
Abstract Polypyrrole (PPy) films were electrochemically synthesized on an Au/TiO2 coated quartz crystal electrode in solutions with different heparin (Hep) concentrations. The PPy films morphology was determined by tapping a mode atomic force microscopy (AFM). The influence of the dopant concentration on the coating surface roughness was studied. Electrochemical quartz crystal microbalance (EQCM) results suggest that Hep retained in the PPy films was bound to thrombin. The adsorbed thrombin amount increased with a higher coating surface roughness. PPy films doped with Hep are electroactive and show cation exchange properties under oxidation or reduction conditions in a Ringer solution. The pre-oxidized PPy film adsorbed a greater thrombin amount than the freshly one and even more than the pre-reduced film.